Pengaruh Massase Punggung Terhadap Penurunan Skala Nyeri Persalinan Kala I Fase Aktif Di UPTD Puskesmas Maga Kab. Mandailing Natal Tahun 2022 - Elfiana Elfiana; Basaria Manurung (Pusat Riset dan Inovasi Nasional, 2023)
Pain in labor is an unpleasant emotional and sensory experience arising from actual or potential tissue damage or demonstrated. Pain is a natural process in labor. If it is not handled properly, it will cause other problems, namely increased anxiety or worry due to lack of knowledge in the mother about the processes that occur when facing labor. This study aims to determine the effect of back massage on reducing the pain scale of labor in the first active phase at UPTD Puskesmas Maga, Mandailing Natal district in 2022. This type of research is a quasi-experimental study with a research approach using a prepost test design with one group test. The population is all pregnant women who are at the UPTD Puskesmas Maga, Mandailing Natal Regency in 2022, totaling 54 mothers in partu. The number of samples used was 54 people obtained by using total sampling technique. The data analysis technique uses the Paired-Samples T Test. The results obtained in this study were from 54 respondents, there was an effect of back massage on a decrease in the active phase of labor pain scale in the first active phase with a value of p = 0.011. There is an Effect of Back Massage on Reducing the Pain Scale of Labor in the Active Phase I. It is recommended for health workers to improve counseling related to reducing the pain of the active phase of labor in the first stage of labor for mothers in labor with back massage